BREEDING METHOD FOR REPLACING YOUNG MINKS WITH REGARD TO FOOD USE EFFICIENCY - O. V. Rastimeshina; T. M. Demina (Вавиловский журнал генетики и селекции)
Selection of pair-kept minks with regard to food use efficiency can be improved by a slight modification of the conventional selection method. The size of each animal should be corrected taking into account the size of its partner in the cage. This method changes the ranks of pedigree value, improving breeding efficiency. The quality of pair selection for mating can be improved by applying the principle «the best with the best». The developed method for selection of replacement young minks according to feed use efficiency increases the live weight return on food by up to 9–10 %.